Dental materials based on polymerizable thiourea derivatives

By using initiator systems of hydroperoxide and specific thiourea derivatives, the problems of incomplete curing of dental materials and discoloration and acid damage in traditional redox systems are solved, and the good curing, mechanical properties and biocompatibility of the materials are achieved. .

CN114848503BActive Publication Date: 2025-02-25IVOCLAR VIVADENT AG
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202210104995.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-05
Filing Date
2022-01-28
Publication Date
2025-02-25
Estimated Expiration
2042-01-28

Smart Images

  • Figure CN114848503B_ABST
    Figure CN114848503B_ABST
Patent Text Reader

Abstract

A free-radical polymerizable dental material comprising a combination of a hydroperoxide and a thiourea derivative according to the following formula (I) as an initiator system for free-radical polymerization: wherein R is absent or is an aromatic, aliphatic, linear or branched C1-C 50 a hydrocarbon group which may be interrupted by one or more ether, thioether, ester, amide or urethane groups; PG is a free-radically polymerizable (meth)acrylate, (meth)acrylamide or vinyl group; and n is 1, 2 or 3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a free-radically polymerizable composition with a hydroperoxide-thiourea redox initiator system, which comprises a free-radically polymerizable thiourea derivative. The composition is particularly suitable as a dental material, for example as a prosthetic material, cement, adhesive and composite material for direct filling. Background Art

[0002] The main areas of use of polymers in the dental field are removable prostheses (e.g. teeth and prosthesis base materials) and fixed prostheses (e.g. facing materials, crowns or cements), filling materials (e.g. direct or indirect filling composites, fixed cements or adhesives) or auxiliary materials (e.g. impression materials). The polymers are usually obtained by free radical polymerization of a composition comprising a polymerizable organic matrix, usually a mixture of monomers, an initiator component and a stabilizer.

[0003] Methyl methacrylate (MMA) (prosthetic materials), functionalized monomers such as, for example, 2-hydroxyethyl methacrylate (HEMA) or acid group-containing adhesive monomers such as 10-methacryloyloxydecyl dihydrogen phosphate (MDP) in mixtures with dimethacrylates (adhesives), or mixtures containing only dimethacrylates (composite cements and filling composites) are usually used as monomers. Frequently used dimethacrylates are 2,2-bis[4-(2-hydroxy-3-methacryloyloxypropyl)phenyl]propane (bis-GMA) and 1,6-bis-[2-methacryloyloxyethoxycarbonylamino]-2,2,4-trimethylhexane (UDMA), which have high viscosity and produce polymers with very good mechanical properties. Most importantly, triethylene glycol dimethacrylate (TEGDMA), 1,10-decanediol dimethacrylate (D3MA) or bis-(3-methacryloyloxymethyl)tricyclo-[5.2.1.02.6]decane (DCP) are used as reactive diluents.

[0004] Dental materials based on methacrylates are cured by free radical polymerization, with photoinitiators (light curing, direct filling composites and adhesives), thermal initiators (indirect composites or prosthetic materials) or redox initiator systems (composite cements) being used, depending on the field of use. Combinations of photoinitiators with redox initiators are also common, for example in the case of filling materials for deep cavities.

[0005] Redox systems are used in particular when there is a risk of incomplete curing, for example in the case of prosthetic materials due to low monomer reactivity or in the case of fixation cements due to insufficient irradiation.

[0006] In order to ensure sufficient storage stability of the material, materials based on redox initiators are usually used as so-called two-component systems (2C systems), in which the oxidant (peroxide or hydroperoxide) and the reducing agent (amine, sulfinic acid, barbiturate, thiourea, etc.) are incorporated into two separate components. These components are mixed with each other shortly before use. The two components must be matched so that they can be easily blended and used uniformly and so that a processing time sufficient for dental purposes is obtained. The processing time refers to the time period between the blending of the two components and the start of curing of the mixed material. On the other hand, the curing time, i.e. the time period until the material is completely hardened, must not be too long.

[0007] For a long time, redox initiator systems based on mixtures of dibenzoyl peroxide (DBPO) and tertiary aromatic amines, such as, for example, N,N-diethanol-p-toluidine (DEPT), N,N-dimethyl-symmetric xylidine (DMSX) or N,N-diethyl-3,5-di-tert-butylaniline (DABA), have been used primarily for dental composite cements. The use of DBPO / amine-based redox initiator systems in combination with phenolic inhibitors allows relatively good setting of the processing and curing times. A disadvantage of such DBPO / amine systems is the discoloration caused by the slow oxidation of the amines. In addition, in the case of DBPO / amine-based redox initiator systems, the formation of free radicals is impaired by acids and therefore also by the acidic monomers that are usually used to prepare enamel-dentine adhesives. The amine component is protonated by an acid-base reaction and is therefore inactivated.

[0008] The above disadvantages can be partially overcome by using a hydroperoxide redox initiator system, since no tertiary amine is required as a reducing agent. In addition, hydroperoxides are more thermally stable than peroxides. For example, the 10-hour half-life temperature T of cumene hydroperoxide is 1 / 2 is 158°C; the 10-hour half-life temperature of DBPO is T 1 / 2 It is only 73℃.

[0009] DE 26 35 595 C2 discloses polymerizable dental filling compounds which comprise a combination of a substituted thiourea reducing agent and a hydroperoxide oxidizing agent as the initiator system. The materials are said to have improved color stability and shelf life and good curing rates.

[0010] EP 1 693 046 B1 discloses dental cements and core building materials which comprise a combination of (2-pyridyl)-2-thiourea derivatives and hydroperoxides, wherein the hydroperoxide groups are bonded to tertiary carbon atoms.

[0011] WO 2007 / 016508 A1 discloses a polymerizable dental composition comprising a combination of a thiourea derivative and a hydroperoxide as an initiator system. The composition does not contain monomers having acid groups.

[0012] According to EP 1 754 465 B1, the reactivity of the cumene hydroperoxide / acetylthiourea system can be increased by adding soluble copper compounds.

[0013] US 7,275,932 B2 proposes the use of hydroperoxides and thiourea derivatives in combination with acidic compounds as accelerators. Preferred acidic compounds are acrylates and methacrylates having an acid group such as, for example, methacrylic acid.

[0014] EP 2 233 544 A1 and EP 2 258 336 A1 disclose dental materials which contain hydroperoxides and thiourea derivatives in combination with vanadium compounds as accelerators.

[0015] WO 03 / 057792 A2 discloses dental materials containing polymerizable thiourea derivatives such as allylthiourea, 1-allyl-3-(2-hydroxyethyl)-2-thiourea or methacrylate 4-oxo-9-thio-5-oxa-3,8,10-triazatridec-12-en-1-yl ester as reducing agents. These would have a lower potential for toxicity or the risk of anesthetic side effects.

[0016] Initiator systems based on hydroperoxides and thiourea derivatives have been of considerable importance in avoiding the disadvantages associated with peroxide / amine systems. The disadvantage is that many thiourea derivatives have a strong bitter taste (D. Mela, Chem. Senses 14 (1989) 131-135; Lange et al., Chem. Amer. Chem. Soc. 51 (1929) 1911-1914; Qin et al., Talanta 199 (2019) 131-139), which is still evident even after hardening, which is considered unpleasant by many patients. Summary of the invention

[0017] The object of the present invention is to provide a dental material which does not have the disadvantages of the prior art. The material does not have a bitter taste, has good biocompatibility and good curing characteristics, and has good mechanical properties.

[0018] This object is achieved by a free-radically polymerizable dental material which comprises, as initiator system for the free-radical polymerization, a combination of a hydroperoxide and a thiourea derivative according to the following formula (I):

[0019]

[0020] where the variables have the following meanings:

[0021] R is absent or is an aromatic, aliphatic, straight or branched C1-C 50 a hydrocarbon radical which may be interrupted by one or more, preferably 1 to 8, particularly preferably 1 to 6, ether, thioether, ester, amide or urethane radicals,

[0022] PG is a free-radically polymerizable (meth)acrylate, (meth)acrylamide or vinyl group, and n is 1, 2 or 3.

[0023] The variables preferably have the following meanings:

[0024] R is an aromatic, aliphatic, straight or branched C1-C 30 a hydrocarbon radical which may be interrupted by one or more, preferably 1 to 6, particularly preferably 1 to 3, ether, ester or urethane radicals,

[0025] PG is a free radical polymerizable methacrylate or vinyl group, and

[0026] n is 1 or 2.

[0027] The variables particularly preferably have the following meanings:

[0028] R is an aliphatic, straight or branched C1-C 20 a hydrocarbon group which may be interrupted by 1 to 6 ether groups or one (1) ester or urethane group,

[0029] PG is a free radical polymerizable methacrylate or vinyl group, and

[0030] n is 1

[0031] or

[0032] R is phenylene, preferably p-phenylene, or a group having the formula -Ph-CH2-,

[0033] PG is a vinyl group and

[0034] n is 1,

[0035] Among them, when R is -Ph-CH2-, the vinyl group is bonded to the phenyl (Ph): H2C=CH-Ph-CH2-.

[0036] All chemical formulae shown herein are extended only to those compounds that are compatible with the chemical valence theory. The indication that a group is separated by, for example, one or more ether groups is understood to mean that these groups are inserted into the carbon chain of the group in each case. Therefore, these groups have C atoms adjacent on both sides and cannot be terminal. C1 groups cannot be separated. Corresponding to the usual nomenclature, aromatic hydrocarbon groups also refer to those groups that contain aromatic and non-aromatic groups. Preferred aromatic groups are, for example, -Ph-CH2-.

[0037] The preferred, particularly preferred and very particularly preferred definitions given for the individual variables can be selected in each case independently of one another. According to the invention, compounds in which all variables have preferred, particularly preferred and very particularly preferred definitions are naturally particularly suitable.

[0038] Thiourea derivatives of formula I are unknown but can be prepared using known synthetic methods. For example, polymerizable benzoyl and acetyl thiourea derivatives can be prepared by reaction of the corresponding polymerizable acid chlorides with thiourea at elevated temperatures:

[0039] Phase 1:

[0040]

[0041] Specific examples:

[0042]

[0043] Phase 2:

[0044]

[0045] Specific examples:

[0046]

[0047]

[0048] Preferred polymerizable thiourea derivatives of formula (I) according to the invention are:

[0049]

[0050]

[0051]

[0052] The polymerizable thiourea derivative of formula (I) according to the present invention is used in combination with a hydroperoxide.

[0053] The hydroperoxides preferred according to the invention are of the formula R 1 (OOH) m A compound wherein R 1 is an aliphatic or aromatic hydrocarbon group and m is 1 or 2. Preferred groups R 1It is an alkyl and aryl group. The alkyl group may be linear, branched or cyclic. The cyclic alkyl group may be substituted by an aliphatic alkyl group. Preferably, the alkyl group has 4 to 10 carbon atoms. The aryl group may be unsubstituted or substituted by an alkyl group. A preferred aromatic hydrocarbon group is a phenyl group substituted by 1 or 2 alkyl groups. The aromatic hydrocarbon group preferably contains 6 to 12 carbon atoms. Particularly preferred hydroperoxides are tert-amyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-butyl hydroperoxide, tert-hexyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, diisopropylbenzene monohydroperoxide, p-menthane hydroperoxide, p-isopropylcumene hydroperoxide and mixtures thereof. Very particularly preferred is cumene hydroperoxide (CHP).

[0054] The low-odor CHP derivatives of formula II disclosed in European patent application EP 3 692 976 A1 are further preferred.

[0055]

[0056] where the variables have the following meanings:

[0057] Q 1 It is a p-valent aromatic, aliphatic, straight-chain or branched C1-C 14 Hydrocarbyl, which may be interrupted by one or more S and / or O atoms and which may be unsubstituted or substituted by one or more preferably selected from -OH, -OR 2 , -Cl and -Br, where R 2 Is aliphatic, straight or branched C1-C 10 Hydrocarbon,

[0058] X and Y are each independently absent, -O-, -COO-; -CONR 3 -or-O-CO-NR 4 -, where R 3 and R 4 each independently represents H or C1-C5 alkyl, preferably H, methyl and / or ethyl, particularly preferably H, and wherein X and Y are preferably not present at the same time,

[0059] Q 2 Absent, aliphatic, straight or branched C1-C 14 Alkylene, which may be interrupted by S and / or O atoms and which may be unsubstituted or substituted by -OH, -OR 5 , -Cl and / or -Br, wherein R 5 Is aliphatic, straight or branched C1-C 10 Hydrocarbon,

[0060] Q 3is C1-C3 alkylene or absent, preferably -CH2- or absent,

[0061] If Q 2 does not exist, then X and / or Y does not exist,

[0062] p is 1, 2, 3 or 4, where

[0063] Substitution on the aromatic compound occurs at the 2, 3 or 4 position relative to the cumene hydroperoxide group.

[0064] The variables preferably have the following meanings:

[0065] Q 1 It is a monovalent or divalent aliphatic, straight or branched chain C1-C 10 A hydrocarbon group which may be interrupted by one or more O atoms, preferably one O atom, and which may be substituted by one or more, preferably one, substituents selected from -OH and -OR 2 , or is preferably unsubstituted, wherein R 2 is an aliphatic, straight-chain or branched C1-C6 hydrocarbon group,

[0066] X and Y are each independently absent, -O-, -COO- or -O-CO-NR 4 -, where R 4 represents H or C1-C5-alkyl, preferably H, methyl and / or ethyl, very particularly preferably H, and wherein X and Y are preferably not present at the same time,

[0067] Q 2 Not present, straight chain or branched C1-C 10 Alkylene, which may be interrupted by one or more O atoms, preferably one O atom, and which may be interrupted by one or more, preferably one, selected from -OH and -OR 5 Substituents are substituted or preferably unsubstituted, wherein R 5 is an aliphatic, straight-chain or branched C1-C6 hydrocarbon group,

[0068] p is 1 or 2, where

[0069] Substitution on the aromatic compound occurs at the 3-position, preferably the 4-position.

[0070] The variables particularly preferably have the following meanings:

[0071] Q 1 is a monovalent or divalent aliphatic, linear or branched C1-C5 hydrocarbon radical, which may be interrupted by one O atom and which may be substituted by one OH group,

[0072] X is -COO-,

[0073] Y does not exist,

[0074] Q 2 does not exist or is a straight chain C1-C3 alkylene group,

[0075] p is 1 or 2, and wherein substitution on the aromatic compound occurs at the 4-position.

[0076] The variables very particularly preferably have the following meanings:

[0077] Q 1 is a monovalent or divalent aliphatic, branched, preferably straight chain C1-C4 hydrocarbon group,

[0078] X is -COO-,

[0079] Y does not exist,

[0080] Q 2 Not present or methylene,

[0081] p is 1 or 2, and wherein substitution on the aromatic compound occurs at the 4-position.

[0082] Preferred hydroperoxide derivatives of formula II according to the invention are:

[0083]

[0084]

[0085]

[0086]

[0087] The hydroperoxide derivatives of the formula II exhibit very good storage stability at room temperature and are particularly suitable as low-odor hydroperoxide components in redox initiator systems for dental compositions. The material according to the invention may comprise one or more hydroperoxides.

[0088] According to a further preferred embodiment, the dental material according to the invention comprises at least one transition metal compound in addition to at least one hydroperoxide and at least one thiourea derivative of formula I. It has been found that the addition of transition metal compounds results in materials having significantly improved mechanical properties after hardening.

[0089] Preferred transition metal compounds according to the invention are compounds derived from transition metals having at least two stable oxidation states. Compounds of elemental copper, iron, cobalt, nickel and manganese are particularly preferred. These metals have the following stable oxidation states: Cu(I) / Cu(II), Fe(II) / Fe(III), Co(II) / Co(III), Ni(II) / Ni(III), Mn(II) / Mn(III). Materials comprising at least one copper compound are particularly preferred.

[0090] The transition metals are preferably used in the form of their salts. Preferred salts are nitrates, acetates, 2-ethylhexanoates and halides, of which chlorides are particularly preferred.

[0091] The transition metals can also be advantageously used in complexed form, with complexes with ligands that form chelates being particularly preferred. Preferred simple ligands for complexing transition metals are 2-ethylhexanoate and THF. Preferred ligands that form chelates are 2-(2-aminoethylamino)ethanol, aliphatic amines, particularly preferably 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA), N,N,N′,N″,N″-pentamethyldiethylenetriamine (PMDETA), tri[2-(dimethylamino)ethyl]amine (Me6TREN), N,N,N′,N′-tetramethylethylenediamine (TMEDA), 1,4,8,11-tetraaza-1,4,8,11-tetramethyl 4-(2-pyridylmethyl)-1 ...

[0092] In the case of electrically neutral ligands, the charge of the transition metal ion must be balanced by suitable counterions. For this purpose, the above-mentioned ions for salt formation come into consideration in particular, with acetates and chlorides being particularly preferred. Chlorides and complexes are characterized by relatively good solubility in the monomers used to prepare dental materials.

[0093] Instead of transition metal complexes, combinations of non-complexed salts of transition metals with organic compounds that form complexes can be used to prepare dental materials, preferably in combination with the above-specified chelate-forming compounds. When mixed with transition metal salts, organic ligands form catalytically active complexes. The use of such combinations of transition metal salts and organic ligands is preferred.

[0094] Metallic copper, preferably Cu + , iron, preferably Fe 3+ , cobalt, preferably Co 3+ , and nickel, preferably Ni 2+ Transition metal compounds of are preferred.

[0095] Preferred copper salts are copper(II) carboxylates (e.g. copper(II) salts of acetic acid or 2-ethylhexanoic acid), CuCl2, CuBr2, CuI2, particularly preferably CuBr and very particularly preferably CuCl. Preferred copper complexes are complexes with the ligands acetylacetone, phenanthroline (e.g. 1,10-phenanthroline (phen)), aliphatic amines such as, for example, 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA), N,N,N′,N″,N″-pentamethyldiethylenetriamine (PMDETA), tris[2-(dimethylamino)ethyl]amine (Me6TREN).

[0096] Preferred iron salts are FeCl3, FeBr2 and FeCl2. Preferred iron complexes are complexes with the ligands acetylacetone, triphenylphosphine, 4,4′-di(5-nonyl)-2,2′-bipyridine (dNbpy) or 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene (PriIm). The complexes Fe(acac)2 and FeCl2(PPh3)2 are very particularly preferred.

[0097] Preferred nickel salts are NiBr2 and NiCl2, and preferred nickel complexes are nickel acetylacetonate and NiBr2(PPh3)2.

[0098] According to the invention, copper compounds, copper complexes, in particular mixtures of copper salts and complexing organic ligands are particularly preferred. Very particular preference is given to monovalent copper (Cu + ), most preferably copper(I) chloride (CuCl). Compositions comprising salts of monovalent copper, in particular CuCl, are characterized by particularly good storage stability.

[0099] The material according to the invention preferably comprises 0.001 to 5% by weight, particularly preferably 0.005 to 3.0% by weight, very particularly preferably 0.1 to 3.0% by weight, of at least one thiourea derivative of the formula (I).

[0100] The one or more hydroperoxides are preferably used in a (total) amount of 0.01 to 5% by weight, particularly preferably 0.05 to 4.0% by weight and very particularly preferably 0.1 to 3.0% by weight.

[0101] The transition metal compounds are preferably used, where applicable, in amounts of 0.0001 to 1% by weight, preferably 0.0005 to 0.5% by weight, particularly preferably 0.0007 to 0.020% by weight.

[0102] Unless otherwise stated, all percentages herein are relative to the total mass of the composition.

[0103] The thiourea derivatives of the formula (I) are particularly suitable in combination with at least one hydroperoxide for curing free-radically polymerizable compositions.

[0104] The material according to the present invention preferably contains at least one free radical polymerizable monomer. Compositions containing at least one monofunctional (meth)acrylate or polyfunctional (meth)acrylate as free radical polymerizable monomer are particularly preferred. Monofunctional (meth)acrylate refers to a compound having one free radical polymerizable group, and polyfunctional (meth)acrylate refers to a compound having two or more, preferably 2 to 4 free radical polymerizable groups. According to a very particularly preferred embodiment, the composition according to the present invention contains at least one dimethacrylate or a mixture of monomethacrylate and dimethacrylate. The material to be hardened intraorally preferably contains monofunctional methacrylate and / or polyfunctional methacrylate as free radical polymerizable monomer.

[0105] Preferred monofunctional or polyfunctional (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, butyl (meth)acrylate, benzyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate or isobornyl (meth)acrylate, p-cumylphenoxyglycol methacrylate (CMP-1E), 2-(2-biphenyloxy)ethyl methacrylate, bisphenol A dimethacrylate, bis-GMA (addition product of methacrylic acid and bisphenol A diglycidyl ether), ethoxylated or propoxylated bisphenol A dimethacrylates such as, for example, 2-[4-(2-methacryloyloxyethoxyethoxy)phenyl]-2-[4-(2-methacryloyloxyethoxy)phenyl]propane (SR-348c from Sartomer; contains 3 ethoxy groups) and 2,2-bis[4-(2-methacryloyloxypropoxy)phenyl]propane, UDMA ( 2-hydroxyethyl methacrylate and 2,2,4-trimethylhexamethylene-1,6-diisocyanate), V-380 (addition product of a mixture of 0.7 mol 2-hydroxyethyl methacrylate and 0.3 mol 2-hydroxypropyl methacrylate and 1 mol α,α,α′,α′-tetramethyl-m-xylene diisocyanate), di-, tri- or tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate and Glycerol dimethacrylate and glycerol trimethacrylate, 1,4-butanediol dimethacrylate, 1,10-decanediol dimethacrylate (D3MA), bis(methacryloyloxymethyl)tricyclo-[5.2.1.02,6]decane (DCP), polyethylene glycol dimethacrylate or polypropylene glycol dimethacrylate such as, for example, polyethylene glycol 200 dimethacrylate or polyethylene glycol 400 dimethacrylate (PEG200DMA or PEG 400DMA) or 1,12-dodecanediol dimethacrylate or mixtures thereof.

[0106] According to one embodiment, in addition to the above-mentioned monomers, the composition according to the invention preferably further comprises one or more free-radically polymerizable monomers containing acid groups (binder monomers). These impart self-adhesive and / or self-etching properties to the material. Therefore, acid-containing monomers are particularly suitable for preparing self-adhesive dental materials such as, for example, fixing cements.

[0107] Preferred acid-containing monomers are polymerizable carboxylic acids, phosphonic acids and phosphates and their anhydrides. Preferred carboxylic acids and carboxylic anhydrides are 4-(methyl)acryloyloxyethyl trimellitic anhydride, 10-methacryloyloxydecylmalonic acid, N-(2-hydroxy-3-methacryloyloxypropyl)-N-phenylglycine, 4-vinylbenzoic acid. Preferred phosphates are 2-methacryloyloxyethylphenyl hydrogen phosphate, 10-methacryloyloxydecyl dihydrogen phosphate (MDP) and dipentaerythritol pentamethacryloyloxy phosphate. Preferred phosphonic acids are 4-vinylbenzylphosphonic acid, 2-[4-(dihydroxyphosphoryl)-2-oxabutyl]-acrylic acid and their amides, esters such as, for example, 2-[4-(dihydroxyphosphoryl)-2-oxabutyl]-acrylic acid-2,4,6-trimethylphenyl ester.

[0108] Particularly preferred acid group-containing monomers are 4-vinylbenzylphosphonic acid, 2-[4-(dihydroxyphosphoryl)-2-oxabutyl]-acrylic acid and their amides, esters such as, for example, 2-[4-(dihydroxyphosphoryl)-2-oxabutyl]-acrylic acid-2,4,6-trimethylphenyl ester, (meth)acrylamide dihydrogen phosphate esters such as, for example, 6-methacrylamide hexyl dihydrogen phosphate or 1,3-bis(methacrylamide)-propane-2-yl-dihydrogen phosphate, and mixtures thereof. These particularly preferred acid group-containing monomers are characterized by a high hydrolytic stability.

[0109] In addition to the initiator system according to the invention, the composition according to the invention can advantageously further comprise an initiator for free-radical photopolymerization. Such compositions are dual-curing, i.e. they can be cured both chemically and by light. Preferred photoinitiators are benzophenone, benzoin and their derivatives, α-diketones and their derivatives such as 9,10-phenanthrenequinone, 1-phenylpropane-1,2-dione, diacetyl and 4,4′-dichlorobenzil. Preference is given to using a combination of camphorquinone (CQ) and 2,2-dimethoxy-2-phenyl-acetophenone with an amine as a reducing agent, such as, for example, ethyl-4-(dimethylamino)-benzoate (EDMAB) or N,N-dimethylaminoethyl methacrylate.

[0110] Those compositions which do not contain amines are preferred according to the invention. Therefore, Norrish Type I photoinitiators are particularly preferred. Norrish Type I photoinitiators do not require an amine component.

[0111] Preferred Norrish I type photoinitiators are acyl or bisacylphosphine oxides. Monoacyltrialkylgermanium, diacyldialkylgermanium and tetraacylgermanium compounds such as, for example, benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)diethylgermanium Tetrabenzoylgermanium and tetrakis(o-methylbenzoyl)germanium are particularly preferred.

[0112] Furthermore, it is also possible to use mixtures of different photoinitiators, such as, for example, bis(4-methoxybenzoyl)diethylgermanium or tetrakis(o-methylbenzoyl)germanium in combination with camphorquinone and ethyl 4-dimethylaminobenzoate.

[0113] Furthermore, the dental material according to the invention may advantageously contain one or more organic or inorganic fillers. Particulate fillers are preferred. Filler-containing compositions are particularly suitable as dental fixing cements or filling compounds.

[0114] Preferred inorganic fillers are oxides such as SiO2, ZrO2 and TiO2 or mixed oxides of SiO2, ZrO2, ZnO and / or TiO2, nanoparticles or fine fillers such as pyrogenic silica or precipitated silica, glass powders such as quartz, glass ceramics, borosilicates or radiopaque glass powders, preferably barium or strontium aluminosilicate glasses, and radiopaque fillers such as ytterbium trifluoride, tantalum (V) oxide, barium sulfate, or mixed oxides of SiO2 with ytterbium (III) oxide or tantalum (V) oxide. The dental material according to the invention may also contain fibrous fillers, nanofibers, whiskers or mixtures thereof. According to a preferred embodiment, the material according to the invention does not contain fluoroaluminosilicate glass, calcium aluminosilicate glass or other fillers that react with organic acids in the sense of acid-base reactions.

[0115] Preferably, the particle size of the oxide is 0.010 to 15 μm, the particle size of the nanoparticles or fine fillers is 10 to 300 nm, the particle size of the glass powder is 0.01 to 15 μm, preferably 0.2 to 1.5 μm, and the particle size of the radiopaque filler is 0.2 to 5 μm.

[0116] Particularly preferred fillers are mixed oxides of SiO2 and ZrO2 with a particle size of 10 to 300 nm, glass powders with a particle size of 0.2 to 1.5 μm, in particular radiopaque glass powders such as barium or strontium aluminosilicate glass, and radiopaque fillers with a particle size of 0.2 to 5 μm, in particular mixed oxides of ytterbium trifluoride and / or SiO2 and ytterbium(III) oxide.

[0117] Furthermore, ground prepolymers or pearl polymers (isofillers) are suitable as fillers. These can consist exclusively of organic polymers, or exclusively of organic polymers which themselves are filled with inorganic fillers such as radiopaque glass powder (multiple glass powders) and ytterbium trifluoride. The monomers and fillers defined above are suitable for the preparation of ground prepolymers and pearl polymers. The composition for the preparation of complete dentures preferably comprises exclusively organic fillers, particularly preferably ground polymers or pearl polymers based on polymethyl methacrylate (PMMA), very particularly preferably pearl polymers based on PMMA as fillers. According to a preferred embodiment, the material according to the invention does not contain polymers having acid groups, in particular polymers having carboxylic acid groups.

[0118] Unless otherwise stated, all particle sizes are weight-average particle sizes, wherein the particle size determination in the range of 0.1 μm to 1000 μm is performed by static light scattering, preferably using a LA-960 static laser scattering particle size analyzer (Horiba, Japan). Here, a laser diode with a wavelength of 655 nm and an LED with a wavelength of 405 nm are used as light sources. The use of two light sources with different wavelengths makes it possible to measure the entire particle size distribution of the sample in only one measurement channel, wherein the measurement is performed in a wet method. For this purpose, an aqueous dispersion of 0.1 to 0.5% of filler is prepared and its scattered light is measured in a flow cell. Scattered light analysis for calculating particle size and particle size distribution is performed according to the Mie theory according to DIN / ISO13320.

[0119] Particle sizes below 0.1 μm are preferably determined by dynamic light scattering (DLS). Particle sizes in the range of 5 nm to 0.1 μm are preferably measured by dynamic light scattering (DLS) of aqueous particle dispersions, preferably using a Malvern Zetasizer Nano ZS (Malvern Instruments, Malvern UK) with a He-Ne laser at a wavelength of 633 nm at 25°C and a scattering angle of 90°.

[0120] Light scattering decreases with decreasing particle size. Particle sizes below 0.1 μm can also be determined by SEM or TEM spectroscopy. Transmission electron microscopy (TEM) is preferably performed with a Philips CM30 TEM at an accelerating voltage of 300 kV. To prepare the sample, a drop of the particle dispersion is applied to a carbon-coated A thick copper grid (mesh size 300) was used and the solvent was evaporated.

[0121] Fillers are divided into macrofillers and microfillers according to their particle size, wherein fillers with an average particle size of 0.2 to 10 μm are called macrofillers and fillers with an average particle size of about 5 to 100 nm are called microfillers. Macrofillers are obtained, for example, by grinding, for example, quartz, radiopaque glass, borosilicate or ceramics, and macrofillers are usually composed of fragments. Microfillers such as mixed oxides can be prepared, for example, by hydrolysis cocondensation of metal alkoxides. Fillers with small particle size have a greater thickening effect.

[0122] In order to improve the bond between the filler particles and the crosslinked polymer matrix, the filler is preferably surface-modified, particularly preferably by silanization, very particularly preferably by free-radically polymerizable silanes, in particular using 3-methacryloxypropyltrimethoxysilane. For the surface modification of non-silicate fillers, for example of ZrO2 or TiO2, functionalized acidic phosphates such as, for example, 10-methacryloxydecyl dihydrogen phosphate can also be used.

[0123] In addition, the dental material according to the invention may contain one or more further additives, in particular stabilizers, colorants, microbicidal active ingredients, additives that release fluoride ions, foaming agents, fluorescent whitening agents, plasticizers and / or UV absorbers. The material according to the invention may also contain one or more organic or inorganic solvents as additives. However, according to a preferred embodiment, the material according to the invention does not contain water.

[0124] Preferred dental materials according to the invention comprise:

[0125] (a) 0.001 to 5.0% by weight, preferably 0.005 to 3.0% by weight, particularly preferably 0.1 to 3.0% by weight, of at least one thiourea derivative of the formula (I),

[0126] (b) 0.01 to 5.0% by weight, preferably 0.05 to 4.0% by weight, particularly preferably 0.1 to 3.0% by weight, of at least one hydroperoxide,

[0127] (c) 5 to 95% by weight, preferably 10 to 95% by weight, particularly preferably 10 to 90% by weight, of at least one free-radically polymerizable monomer,

[0128] (d) 0 to 80% by weight of filler(s), and

[0129] (e) 0.01 to 5% by weight, preferably 0.1 to 3% by weight, particularly preferably 0.1 to 2% by weight, of additive(s).

[0130] Unless otherwise stated, all amounts herein are relative to the total mass of the composition.

[0131] The filling level is adapted to the desired intended use of the material. Preferably, the filler content of the filling composite material is 50 to 80% by weight, particularly preferably 70 to 80% by weight, and the filler content of the dental cement is 10 to 70% by weight, particularly preferably 60 to 70% by weight. The prosthetic material preferably has a filler content of 0 to 10% by weight, particularly preferably 0 to 5% by weight.

[0132] Particularly preferred dental materials additionally comprise:

[0133] (f) 0.0001 to 1% by weight, preferably 0.0005 to 0.5% by weight, particularly preferably 0.0007 to 0.02% by weight, of at least one transition metal compound.

[0134] Those dental materials consisting of the components mentioned are particularly preferred, wherein the individual components are preferably in each case selected from the above-mentioned preferred and particularly preferred substances. In all cases, mixtures of several substances, such as mixtures of monomers, can also be used as the respective components.

[0135] The material according to the invention is preferably present in the form of two separate components, wherein the first component comprises a hydroperoxide (catalyst paste) and the second component comprises a thiourea derivative (base paste). Since the components preferably have a pasty consistency, they are also referred to herein as pastes. The composition of the catalyst paste and the base paste differs essentially in that the catalyst paste comprises one or more hydroperoxides and the base paste comprises one or more thiourea derivatives.

[0136] The pastes are mixed with each other for use, thereby initiating a hardening reaction. It is preferred that the pastes are blended so that the catalyst paste and the base paste can be used in a volume ratio of 1: 1. After the pastes are mixed, the material has the above-mentioned composition.

[0137] The dental materials according to the invention are characterized in particular in that they do not have a bitter taste after hardening. In addition, they have good curing properties, i.e. they have a combination of a favorable processing time and a favorable curing time. Furthermore, after hardening, the materials have mechanical properties comparable to those of materials based on established redox systems such as, for example, a mixture of acetylthiourea and cumene hydroperoxide (CHP), without restrictions.

[0138] The compositions according to the invention are particularly suitable for use as dental materials, in particular as dental cements, filling composites and facing materials and for the preparation of prostheses, artificial teeth, inlays, onlays, crowns and bridges. The compositions are mainly suitable for intraoral application by dentists for repairing damaged teeth, i.e. for therapeutic applications, for example as dental cements, filling composites and facing materials. However, they can also be used non-therapeutically (extraorally), for example, for the manufacture or repair of dental restorations, such as prostheses, artificial teeth, inlays, onlays, crowns and bridges. DETAILED DESCRIPTION

[0139] The present invention will be explained in more detail below with reference to examples of the embodiments:

[0140] Example

[0141] Example 1

[0142] Synthesis of N-(2-methacryloyloxyhexanoyl)-thiourea

[0143]

[0144] Stage 1: tert-Butyl 6-Hydroxyhexanoate

[0145]

[0146] ε-Caprolactone (181.88 g, 1.59 mol) was dissolved in tert-butanol (1600 ml). Potassium tert-butoxide (196.68 g, 1.75 mol) was added and the suspension was heated to reflux for 5 hours. After cooling, toluene (1600 ml) and water (800 ml) were added and phase separation was performed. The organic phase was washed with water (2 x 1000 ml) and saturated aqueous sodium chloride solution (1000 ml), dried over anhydrous sodium sulfate, filtered and concentrated on a rotary evaporator. The crude product was purified by means of vacuum distillation (boiling point: 70 ° C / 0.03 mbar). 56.57 g (0.30 mol; 19% yield) of colorless liquid was obtained.

[0147] 1 H-NMR (CDCl3, 400MHz): δ = 3.63 (t, 2H; J = 6.6Hz; O-CH2), 2.67 (d, 1H; J = 0.8Hz; OH), 2.22 (t, 2H; J=7.4Hz; (C=O)CH2), 1.63–1.56 (m, 4H; CH2), 1.44 (s, 9H; CH3), 1.43–1.34 (m, 2H; CH2).

[0148] 13 C-NMR (CDCl3, 100.6MHz): δ = 173.2 (C = O), 80.0 (C), 62.3 (CH2), 35.4 (CH2), 32.2 (CH2), 28.0 (CH3), 25.1 (CH2), 24.6 (CH2).

[0149] Second stage: tert-butyl 6-methacryloyloxyhexanoate

[0150]

[0151] A solution of tert-butyl 6-hydroxyhexanoate (11.15 g, 59.2 mmol), triethylamine (7.18 g, 71.0 mmol) and N,N-dimethylaminopyridine (0.36 g, 3.0 mmol) in toluene (50 ml) was cooled to 0°C. A solution of methacrylic anhydride (10.95 g, 71.0 mmol) in toluene (10 ml) was added dropwise, and the reaction mixture was stirred at 0°C for 1 h and at ambient temperature for 1 h. The reaction solution was washed with hydrochloric acid (1 N, 3 x 100 ml), sodium hydroxide solution (1 N, 3 x 100 ml), water (2 x 100 ml) and saturated aqueous sodium chloride solution (100 ml), dried over anhydrous sodium sulfate, filtered and concentrated on a rotary evaporator. 14.35 g (56.0 mmol; 95% yield) of a colorless liquid was obtained.

[0152] 1 H-NMR (CDCl3, 400MHz): δ = 6.09 (m, 1H; = CH), 5.54 (m, 1H; = CH), 4.15 (t, 2H; J = 6.5Hz; O-CH2), 2.23 (t, 2H; J=7.4Hz; (C=O)CH2),1.94(m,3H;CH3),1.74–1.60(m,4H;CH2),1.44(s,9H;CH3),1.43–1.37(m,2H;CH2).

[0153] 13 C-NMR (CDCl3, 100.6MHz): δ = 172.8 (C = O), 167.3 (C = O), 136.4 ( = C), 125.1 ( = CH2), 79.9 ( C),64.4(CH2),35.3(CH2),28.2(CH2),28.0(CH3),25.4(CH2),24.6(CH2),18.2(CH3).

[0154] Stage 3: 6-Methacryloyloxyhexanoic acid

[0155]

[0156] Tert-butyl 6-methacryloyloxyhexanoate (8.79 g, 34.3 mmol) was dissolved in dichloromethane (100 ml) and trifluoroacetic acid (20 ml) was added. The reaction mixture was stirred at ambient temperature. After 18 hours, the solution was concentrated on a rotary evaporator. The trifluoroacetic acid residues were removed by azeotropic distillation with toluene to obtain 6.87 g (34.3 mmol; 100% yield) of a light yellow liquid.

[0157] 1H-NMR (CDCl3, 400MHz): δ = 11.40 (br s,1H; OH), 6.10 (m, 1H; = CH), 5.56 (m, 1H; = CH), 4.16 (t, 2H; J = 6.5Hz; O-CH2), 2.39 (t, 2H ; J=7.4Hz; (C=O)CH2), 1.94 (m, 3H; CH3), 1.76–1.66 (m, 4H; CH2), 1.49–1.41 (m, 2H; CH2).

[0158] 13 C-NMR (CDCl3, 100.6MHz): δ = 179.7 (C = O), 167.6 (C = O), 136.2 ( = C), 125.4 ( = CH2), 64.4 (CH2), 33.7 (CH2), 28.1 (CH2), 25.3 (CH2), 24.1 (CH2), 18.1 (CH3).

[0159] Stage 4: 6-Methacryloyloxyhexanoyl chloride

[0160]

[0161] Oxalic acid dichloride (5.15 g, 40.6 mmol) was added dropwise to a solution of 6-methacryloyloxyhexanoic acid (6.77 g, 33.8 mmol) and N,N-dimethylformamide (0.1 ml) in dichloromethane (100 ml). The reaction solution was stirred at ambient temperature for 3 hours and then concentrated on a rotary evaporator. 7.18 g (32.8 mmol; 97% yield) of a light yellow liquid was obtained.

[0162] 1 H-NMR (CDCl3, 400MHz): δ = 6.08 (m, 1H; = CH), 5.56 (m, 1H; = CH), 4.15 (t, 2H; J = 6.5Hz; O-CH2), 2.9 3(t,2H;J=7.4Hz;(C=O)CH2),1.94(m,3H;CH3),1.80–1.68(m,4H;CH2),1.50–1.43(m,2H;CH2).

[0163] 13 C-NMR (CDCl3, 100.6MHz): δ=173.4(C=O), 167.2(C=O), 136.2(=C), 125.2(=CH2), 64.0(CH2), 46.7(CH2), 28.0(CH2), 24.7(CH2), 24.5(CH2), 18.1(CH3).

[0164] Stage 5: N-(2-methacryloyloxyhexanoyl)-thiourea

[0165]

[0166] 6-Methacryloyloxyhexanoyl chloride (7.05g, 32.2mmol) was dissolved in toluene (80ml). Thiourea (2.70g, 35.5mmol) was added and the suspension was heated to reflux for 3 hours. After cooling, the suspension was filtered. The filtered residue was washed with toluene (100ml) and dried, suspended in water (100ml), filtered, washed with water (2x50ml) and dried. The pale yellow solid was dissolved in toluene (50ml) at 60°C. The solution was cooled to 0°C and cold filtered. The filtered residue was washed with cold toluene (2x10ml) and dried. 1.18g (4.6mmol; 14% yield) of a white solid (melting point: 97°C) was obtained.

[0167] 1 H-NMR (CDCl3, 400MHz): δ = 9.95 (br s, 1H; NH), 9.61 (br s, 1H; NH), 7.54 (br s,1H; NH), 6.10 (s, 1H; = CH), 5.56 (s, 1H; = CH), 4.16 (t, 2H; J = 6.5Hz; O-CH2), 2.41 (t, 2H ; J=7.4Hz; (C=O)CH2), 1.94 (s, 3H; CH3), 1.77–1.64 (m, 4H; CH2), 1.50–1.39 (m, 2H; CH2).

[0168] 13 C-NMR (CDCl3, 100.6MHz): δ = 182.0 (C = S), 173.8 (C = O), 167.5 (C = O), 136.3 ( = C), 12 5.4(=CH2),64.2(CH2),36.8(CH2),28.1(CH2),25.3(CH2),24.1(CH2),18.2(CH3).

[0169] Example 2

[0170] Synthesis of N-(4-vinylbenzoyl)-thiourea

[0171]

[0172] Stage 1: 4-Vinylbenzoyl chloride

[0173]

[0174] Dichloromethane (100 ml) and N,N-dimethylformamide (0.1 ml) were added to 4-vinylbenzoic acid (16.00 g, 0.108 mol), and oxalic acid dichloride (16.45 g, 0.130 mol) was added dropwise. The reaction mixture was stirred at room temperature for 4 hours and then filtered through silica gel. The filtrate was concentrated on a rotary evaporator to obtain 16.51 g (99.0 mmol; 92%) of a light brown liquid.

[0175] 1 H-NMR (CDCl3, 400MHz): δ = 8.05 (d, 2H; J = 8.5Hz; Ar-H), 7.50 (d, 2H; J = 8.4Hz; Ar-H), 6. 75 (dd, 1H; J = 10.9 Hz, 17.6; = CH), 5.93 (d, 1H; J = 17.6; = CH), 5.48 (d, 1H; J = 10.9; = CH).

[0176] 13 C-NMR (CDCl3, 100.6MHz): δ=167.8 (C=O), 144.3 (Ar-C), 135.3 (=CH), 132.0 (Ar-C), 131.8 (Ar-CH), 126.5 (Ar-CH), 118.4 (=CH2).

[0177] Second stage: N-(4-vinylbenzoyl)-thiourea

[0178]

[0179] 4-Vinylbenzoyl chloride (16.41 g, 98.5 mmol) was dissolved in toluene (150 ml) and thiourea (8.25 g, 0.108 mol) was added. The suspension was heated to reflux for 5 hours and filtered after cooling. The filtered residue was washed with toluene (100 ml), water (300 ml) was added, and heated to 60 ° C. After cooling, the suspension was filtered. The filtered residue was washed with water (5x100 ml) and dried. Dichloromethane (500 ml) was added to the pale yellow solid and heated to reflux. The suspension was filtered. The filtrate was concentrated on a rotary evaporator. The pale yellow solid was dissolved in ethyl acetate (100 ml) and filtered through silica gel. The filtrate was concentrated on a rotary evaporator to obtain 3.90 g (18.9 mmol; 19%) of a white solid.

[0180] 1H-NMR (DMSO-d6, 400MHz): δ = 11.25 (s, 1H; NH), 9.91 (s, 1H; NH), 9.60 (s, 1H; NH), 7.95 (d, 2H; J = 8.4Hz; Ar-H), 7.6 1 (d, 2H; J=8.4Hz; Ar-H), 6.82 (dd, 1H; J=10.9Hz, 17.7; =CH), 6.02 (d, 1H; J=17.5; =CH), 5.44 (d, 1H; J=11.2; =CH).

[0181] 13 C-NMR (DMSO-d6, 100.6MHz): δ = 182.5 (C = S), 167.8 (C = O), 141.9 (m, Ar-C), 136 .9(m,=CH),135.4(m,Ar-C),131.7–125.3(m,Ar-CH),119.4–116.2(m,=CH2).

[0182] Example 3

[0183] N-(2-Methacryloyloxyethoxysuccinyl)-thiourea

[0184]

[0185] Stage 1: 3-(2-methacryloyloxyethoxycarbonyl)propionyl chloride

[0186]

[0187] Mono(methacryloyloxyethyl) succinate (11.51 g, 50.0 mmol) was dissolved in dichloromethane (80 ml). N,N-dimethylformamide (0.1 ml) was added and oxalic acid dichloride (6.35 g, 50.0 mmol) was added dropwise. The reaction solution was stirred at ambient temperature for 3 hours and then concentrated on a rotary evaporator. 12.39 g (49.8 mmol; 100%) of a colorless liquid was obtained.

[0188] 1 H-NMR (CDCl3, 400MHz): δ=6.03 (s, 1H; =CH), 5.61 (s, 1H; =CH), 4.37 (s, 4H; OCH2), 3.23 (t, 2H; J = 6.5Hz; CH2), 2.72 (t, 2H; J = 6.5Hz; CH2), 1.95 (s, 3H; CH3).

[0189] 13C-NMR (CDCl3, 100.6MHz): δ=172.8(C=O), 170.5(C=O), 166.9(C=O), 135.7(=C) ,126.1(=CH2),62.7(O-CH2),62.0(O-CH2),41.5(CH2),29.1(CH2),18.1(CH3).

[0190] Second stage: N-(2-methacryloyloxyethoxysuccinyl)-thiourea

[0191]

[0192] 3-(2-Methacryloyloxyethoxycarbonyl)propionyl chloride (12.43 g, 50.0 mmol) was dissolved in toluene (100 ml). Thiourea (4.19 g, 55.0 mmol) was added, and the suspension was heated under reflux for 2 hours. After cooling, the suspension was filtered. The filtration residue was washed with toluene (100 ml) and dried to obtain 2.44 g (8.4 mmol; 17%) of a white solid (melting point: 151° C.).

[0193] 1 H-NMR (DMSO-d6, 400MHz): δ = 11.18 (s, 1H; NH), 9.53 (s, 1H; NH), 9.35 (s, 1H; NH), 6.03 (m, 1H; =CH), 5.69 (m, 1H; =CH), 4.28 (s, 4H; O-CH2), 2.71–2.54 (m, 4H; CH2), 1.88 (s, 3H; CH3).

[0194] 13 C-NMR (DMSO-d6, 100.6MHz): δ = 182.0 (C = S), 173.7 (C = O), 172.4 (C = O), 166.8 (m, C = O), 135 .6(m,=C),128.0(m,=CH2),126.4(m,=CH2),62.6(m,O-CH2),30.0(m,N-CH2),17.7(CH3).

[0195] Example 4 (Comparative Example)

[0196] Synthesis of 4-oxo-9-thioxo-5-oxa-3,8,10-triazatridec-12-en-1-yl methacrylate

[0197]

[0198] N-allyl-N'-(2-hydroxyethyl)thiourea (8.01 g, 50.0 mmol) was dissolved in anhydrous tetrahydrofuran (80 ml) and isocyanatoethyl methacrylate (7.76 g, 50.0 mmol) was added dropwise. Dibutyltin dilaurate (0.24 g, 2.0 mmol) was added and the reaction mixture was stirred at room temperature. After 20 hours, the clear colorless solution was concentrated on a rotary evaporator. The colorless oil was dissolved in ethyl acetate (50 ml) and filtered through silica gel. The filtrate was concentrated on a rotary evaporator to give 15.45 g (48.9 mmol; 98%) of a waxy white solid.

[0199] 1 H-NMR (CDCl3, 400MHz): δ = 7.04–6.65 (m, 2H; NH), 6.13 (s, 1H; = CH), 5.92–5.80 (m, 1H; = CH), 5.62 (s, 1H; = CH), 5. 60–5.49(m,1H;NH),4.34–4.19(m,4H;CH2),4.19–3.64(m,4H;CH2),3.54–3.32(m,2H;N-CH2),1.95(s,3H;CH3).

[0200] 13 C-NMR (CDCl3, 100.6MHz): δ=182.0 (C=S), 167.3 (C=O), 156.7 (C=O), 135.6 (=C), 133.1 (=CH), 126.2 (=CH2 ), 117.0 (=CH2), 63.3 (m, O-CH2), 63.2 (m, O-CH2), 46.4 (N-CH2), 44.4 (N-CH2), 40.1 (N-CH2), 18.1 (CH3).

[0201] Example 5

[0202] Thiourea-based composite cement according to the present invention

[0203] Chemically curing composite cements, each consisting of a base paste and a catalyst paste, were prepared from a mixture of the dimethacrylate UDMA (addition product of 2-hydroxyethyl methacrylate and 2,2,4-trimethylhexamethylene-1,6-diisocyanate), bis-GMA (addition product of methacrylic acid and bisphenol A diglycidyl ether) and 2-(2-biphenyloxy)ethyl methacrylate (MA-836) as well as stabilizers MEHQ (hydroquinone monomethyl ether) and TEMPO (2,2,6,6-tetramethylpiperidin-1-yl)oxy), filler GM27884 0.7 μm sil. (silanized glass filler GM G018-056, average particle size 0.7 μm, Schott) and the initiator component CHP (cumene hydroperoxide, 80%), copper(II) acetylacetonate (Cu(acac)2) and in each case a thiourea compound.

[0204] Table 1: Composition of catalyst paste Cat-1

[0205] Components Ratio (weight %) Dual-GMA 10.020 UDMA 13.352 MA-836 10.020 CHP 1.590 MEHQ 0.018 GM27884 0.7um sil. 65.000 total 100.00

[0206] Table 2: Composition of the basic paste

[0207]

[0208] *) Comparative Example

[0209] Catalyst paste Cat-1 was blended with various base pastes in a volume ratio of 1:1, and the processing time of the resulting cement was determined. The processing time (PT) of the paste mixture was determined by means of a rheometer (Motion Compact Rheometer MCR 302, Anton Paar). To this end, the catalyst paste and the base paste were manually blended in a ratio of 1:1 on a mixing block. The material was then applied to a mold consisting of Delrin with a rough surface on the rheometer. The measuring pendulum fixed on the spindle with the same rough surface compressed the sample and determined the storage modulus by slight rotation. At the beginning of the stable phase and after reaching a specific gradient, an inflection point was defined in each case. The inflection points were then connected by a straight line. The measuring point farthest from this straight line was defined as PT. The entire measurement was carried out in a temperature-controlled room at 28.7°C. The results are listed in Table 3.

[0210] Table 3: Processing time (PT) of cement

[0211]

[0212] *) Comparative Example

[0213] The flexural strength and flexural modulus of the cement were determined according to the EN ISO-4049 standard (dental-polymer-based filling, restorative and adhesive materials). For this purpose, the catalyst paste Cat-1 was blended with various base pastes in a volume ratio of 1:1 in each case, and test pieces conforming to the standard were prepared from the mixture. These were cured by storage in a heating chamber at 37°C for 45 minutes and then the mechanical properties were measured. The results are collated in Table 4.

[0214] The results demonstrate that, after hardening, the composite cement according to the invention has much better mechanical properties than comparative materials with known polymerizable thiourea derivatives, which are comparable in every respect to the mechanical properties of cements based on the tried and tested CHP initiator system with hexanoylthiourea.

[0215] Table 4: Flexural strength (FS, MPa) and flexural modulus (FM, MPa) of hardened cement

[0216]

[0217] *) Comparative Example

[0218] a) DS: dry storage at room temperature for 24 hours

[0219] b) WS: water stored at 37°C for 24 hours.

Claims

1. A free-radically polymerizable dental material comprising a combination of a thiourea derivative and a hydroperoxide as an initiator system for free-radical polymerization, characterized in that It comprises a thiourea derivative according to the following formula (I): Where the variables have the following meanings: R is an aromatic or aliphatic straight or branched C1-C 20 a hydrocarbon group which is uninterrupted or interrupted by 1 to 6 ether groups or one (1) ester group, PG is a free radical polymerizable methacrylate or vinyl group, n is 1, And, it contains the formula R 1 -(OOH) m Hydroperoxides, where R 1 is an aliphatic or aromatic hydrocarbon group and m is 1 or 2, and The dental material further comprises at least one free-radically polymerizable monomer which is selected from monofunctional (meth)acrylates or polyfunctional (meth)acrylates.

2. The dental material according to claim 1, wherein The variables in formula (I) have the following meanings: R is a phenylene group or a group having the formula -Ph-CH2-, PG is a vinyl group, and n is 1.

3. The dental material according to claim 1, comprising as the hydroperoxide tert-amyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-butyl hydroperoxide, tert-hexyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, diisopropylbenzene monohydroperoxide, p-menthane hydroperoxide, p-isopropylcumene hydroperoxide or a mixture thereof.

4. The dental material according to claim 1, comprising cumene hydroperoxide (CHP) as the hydroperoxide.

5. The dental material according to claim 1, further comprising a transition metal compound.

6. Dental material according to claim 5, comprising a transition metal compound having at least two stable oxidation states. 7 . The dental material according to claim 5 , comprising a copper compound, an iron compound, a cobalt compound, a nickel compound, a manganese compound or a mixture thereof.

8. The dental material according to claim 1 , comprising, in each case relative to the total mass of the material: - 0.001 to 5% by weight of at least one thiourea derivative of formula (I), - 0.01 to 5% by weight of at least one compound of the formula R 1 -(OOH) m Hydroperoxides, - Optionally 0.0001 to 1% by weight of at least one transition metal compound.

9. The dental material according to claim 1 , comprising, in each case relative to the total mass of the material: - 0.005 to 3.0% by weight of at least one thiourea derivative of formula (I), - 0.05 to 4.0% by weight of at least one compound of formula R 1 -(OOH) m Hydroperoxides, - Optionally 0.0005 to 0.5% by weight of at least one transition metal compound.

10. The dental material according to claim 1 , comprising, in each case relative to the total mass of the material: - 0.1 to 3.0% by weight of at least one thiourea derivative of formula (I), - 0.1 to 3.0% by weight of at least one compound of the formula R 1 -(OOH) m Hydroperoxides, - Optionally 0.0007 to 0.020% by weight of at least one transition metal compound.

11. The dental material according to claim 1, comprising at least one dimethacrylate or a mixture of monomethacrylate and dimethacrylate.

12. The dental material according to claim 1, comprising methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, butyl (meth)acrylate, benzyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate or isobornyl (meth)acrylate, p-cumylphenoxyglycol methacrylate, 2-(2-biphenyloxy)ethyl methacrylate, bisphenol A dimethacrylate, an addition product of methacrylic acid and bisphenol A diglycidyl ether, ethoxylated or propoxylated bisphenol A dimethacrylate, 2-[4-(2-methacryloyloxyethoxyethoxy)phenyl]-2-[4-(2-methacryloyloxyethoxy)phenyl]propane), 2,2-bis[4-(2-methacryloyloxypropoxy)phenyl]propane, 2-hydroxyethyl methacrylate and 2,2,4-trimethylhexamethylene-1,6- The free radical polymerizable monomer may be an addition product of a diisocyanate, an addition product of a mixture of 0.7 mol of 2-hydroxyethyl methacrylate and 0.3 mol of 2-hydroxypropyl methacrylate and 1 mol of α,α,α′,α′-tetramethyl-m-xylene diisocyanate, di-, tri- or tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, glycerol dimethacrylate and glycerol trimethacrylate, 1,4-butanediol dimethacrylate, 1,10-decanediol dimethacrylate, bis(methacryloyloxymethyl)tricyclo-[5.2.1.02,6]decane, polyethylene glycol dimethacrylate or polypropylene glycol dimethacrylate, polyethylene glycol 200 dimethacrylate, polyethylene glycol 400 dimethacrylate, 1,12-dodecanediol dimethacrylate or a mixture thereof.

13. The dental material according to claim 1, further comprising at least one free-radically polymerizable monomer containing acid groups.

14. Dental material according to claim 13, comprising a polymerizable carboxylic acid, a phosphonic acid, a polymerizable phosphoric acid ester or anhydrides of these substances.

15. Dental material according to any one of claims 1 to 5, further comprising at least one organic or inorganic filler.

16. The dental material according to claim 15, wherein the inorganic filler is selected from oxides, fine fillers, glass powders, radiopaque fillers or mixtures thereof, the oxides are selected from SiO2, ZrO2, TiO2 or mixed oxides of SiO2, ZrO2, ZnO and / or TiO2, the fine fillers are selected from pyrogenic silica or precipitated silica, the glass powders are selected from quartz, glass ceramics, radiopaque glass powders, and the radiopaque fillers are selected from ytterbium trifluoride, tantalum (V) oxide, barium sulfate, mixed oxides of SiO2 and ytterbium (III) oxide or tantalum (V) oxide.

17. The dental material according to claim 15, comprising a radiopaque glass powder selected from barium aluminosilicate or strontium aluminosilicate glass powder.

18. The dental material according to claim 15, comprising a ground prepolymer or pearl polymer.

19. The dental material according to claim 15, comprising nanoparticles selected from fumed silica or precipitated silica.

20. The dental material according to any one of claims 1 to 5, comprising, in each case relative to the total mass of the material: (a) 0.001 to 5.0% by weight of at least one thiourea derivative of the formula (I), (b) 0.01 to 5.0% by weight of at least one compound of the formula R 1 -(OOH) m Hydroperoxides, (c) 5 to 95% by weight of the at least one free-radically polymerizable monomer, (d) 0 to 80% by weight of one or more fillers, and (e) 0.01 to 5% by weight of one or more additives.

21. The dental material according to claim 20, comprising in each case, relative to the total mass of the material (a) 0.005 to 3.0% by weight of at least one thiourea derivative of the formula (I), (b) 0.05 to 4.0% by weight of at least one compound of formula R 1 -(OOH) m Hydroperoxides, (c) 10 to 95% by weight of the at least one free-radically polymerizable monomer, (d) 0 to 80% by weight of one or more fillers, and (e) 0.1 to 3% by weight of one or more additives.

22. The dental material according to claim 20, comprising in each case, relative to the total mass of the material (a) 0.1 to 3.0% by weight of at least one thiourea derivative of the formula (I), (b) 0.1 to 3.0% by weight of at least one compound of the formula R 1 -(OOH) m Hydroperoxides, (c) 10 to 90% by weight of the at least one free-radically polymerizable monomer, (d) 0 to 80% by weight of one or more fillers, and (e) 0.1 to 2% by weight of one or more additives.

23. The dental material according to claim 20, wherein the dental material is used as a filling composite and comprises 50 to 80% by weight of one or more fillers, the dental material is used as a dental cement and comprises 10 to 70% by weight of one or more fillers, or the dental material is used as a prosthetic material and comprises 0 to 10% by weight of one or more fillers.

24. Non-therapeutic use of the dental material according to any one of claims 1 to 23 for the extraoral preparation or repair of a dental restoration, wherein the dental restoration is selected from the group consisting of a prosthesis, an artificial tooth, an inlay, an onlay, a crown, a bridge and a complete denture.

Citation Information

Patent Citations

  • Collection and transport vehicle for domestic waste

    EP0550056A1

  • Acid tolerant dental composition

    EP1693046B1

  • 2-component initiator system (amine free) with storage stability and especially suitable for acidic systems

    EP1754465B1

  • Dental primer and dental adhesive set

    EP2258336A1

  • Dental materials based on redox systems with low odor cumolhyde-hydroperoxide derivatives

    EP3692976A1